Program Kampus Mengajar Untuk Meningkatkan Literasi Dan Numerasi Di SD Pakis Gelora Surabaya - Lisrotul Munawaroh (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
The teaching campus is a program from the Ministry of Research and Technology that provides opportunities for students to study off campus for one semester. Through the campus teaching program, students have activities that are their responsibility in assisting learning activities at school. In this program, students become partners with teachers to improve literacy and numeracy in schools that are targeted for campus teaching. The main task of this teaching campus program is to assist teachers in implementing learning in schools, especially to improve literacy and numeracy, increase students' creativity and help students adapt technology. The Teaching Campus Program by sending students as school change agents has helped the implementation of teaching and learning activities.